2012
DOI: 10.3109/2000656x.2012.698416
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal compared with postnatal cleft diagnosis: What do the parents think?

Abstract: Since the 1980s, prenatal detection of cleft lip with or without cleft palate (CLP) is possible with a transabdominal ultrasound. The improvement of prenatal detection has resulted in an increased demand for prenatal information and counselling. The aim of this study was to, by means of a questionnaire, evaluate how families, who received the diagnosis prenatally and postnatally, respectively, think about the prenatal and postnatal consultation. Patients referred prenatally or postnatally to the department, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 23 publications
1
16
0
1
Order By: Relevance
“…Regarding preferences for prenatal or postnatal counselling, there were mixed results from two studies involving parents of children with CLP. Berggren et al . found no difference in satisfaction with clinical care between parents who received prenatal versus postnatal counselling; however, 57% of parents who learned of the diagnosis after delivery would have preferred to receive the baby's diagnosis prenatally.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding preferences for prenatal or postnatal counselling, there were mixed results from two studies involving parents of children with CLP. Berggren et al . found no difference in satisfaction with clinical care between parents who received prenatal versus postnatal counselling; however, 57% of parents who learned of the diagnosis after delivery would have preferred to receive the baby's diagnosis prenatally.…”
Section: Resultsmentioning
confidence: 99%
“…It is the counselor's responsibility to inform parents about the etiology, pathogenesis, and associated anomalies; and the medical, surgical, and clinical needs of a child with an oral cleft. However, a former study showed that many parents were unsatisfied with the initial information they received at the ultrasound unit. In the study by Hsieh and Rey‐Bellet, some mothers expressed feeling anxious about their baby's condition, and, because of the limited information provided by professionals, some even feared that the condition might be associated with impaired intelligence.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, participants were included during pregnancy, and although TOP was not standardly discussed, the option to terminate the pregnancy was realistic at 20 weeks of gestation. Because previous studies concerning coping with the prenatal diagnosis of clefts were of retrospective and cross-sectional design (Maes et al, 1998;Matthews et al, 1998;Berk et al, 1999;Davalbhakta and Hall, 2000;Johnson, 2003;Rey-Bellet and Hohlfeld, 2004;Nusbaum et al, 2008;Berggren et al, 2012), their results not only might contain ascertainment bias but also might have influenced parental attitudes toward OC because the children were already born and/or treated (surgically). Furthermore, in contrast to other studies, the process of counseling in our study was uniform because there was always a plastic surgeon and psychologist from the cleft lip and palate team involved (Nusbaum et al, 2008;Berggren et al, 2012).…”
Section: Methodological Issuesmentioning
confidence: 99%